High-risk Human Papillomavirus Testing for Triage of Women with Previous Cytological Abnormalities from the Vale do Ribeira Region - Lorente, Sandra; Fernandes, Natália Coelho Couto de Azevedo; Etlinger-Colonelli, Daniela; Réssio, Rodrigo Albergaria; Oliveira, Sonia Maria Pereira de; Catarino, Regina Maria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To evaluate the performance of the hybrid capture 2 (HC2) high-risk papillomavirus (hrHPV) assay and cytological test in women with previous abnormalities, to detect cervical intraepithelial neoplasia grade 2 or worse (≥ CIN 2).Methods A cytological test and HC2 (Qiagen, Gaithersburg, Maryland, EUA) for hrHPV were conducted in 359 liquid-based (Sure Path, Becton Dickinson, TriPath Imaging, Burlington, NC, USA) samples collected from women from the Vale do Ribeira Region, during July 2013 and September 2015 with previous cytology classified as atypical squamous cells of undetermined significance (ASC-US), low-grade squamous intraepithelial lesion (LSIL), atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesions (ASC-H), and atypical glandular cells (AGC). The histopathological examination was conducted in 179 women. The performance evaluations were calculated using the “exact” Clopper-Pearson 95% confidence interval (CI) test by MEDCALC (Medcalc Software Ltd, Ostend, Belgium).Results The ≥ CIN 2 frequency was 11.7% (21/179). The HC2 for hrHPV and repeat cytology to detect ≥ CIN 2 obtained, respectively, a sensitivity of 90.5% (95%CI = 69.6–98.8) and 90.5%, (95%CI = 69.6–98.8), a specificity of 65.8% (95% CI = 57.9–73.2) and 43.7% (95%CI = 35.8–51.8), a positive predictive value of 26.0% (95% CI = 21.4–31.3) and 17.6%, (95%CI = 14.9–20.6), and a negative predictive value of 98.1% (95%CI = 93.3–99.5) and 97.2% (95% CI = 90.1–99.2).Conclusion Hybrid capture 2 for hrHPV improves the performance of the detection of ≥ CIN 2, without compromising sensitivity, and provides a greater safety margin to return to the triennial screening of women undergoing follow-up due to previous abnormalities, without underlying ≥ CIN 2.
Keywords: human papillomavirus; screening; cervical cancer; papanicolaou test